The influence of type of high school attended on university performance - Birch, E.; Miller, Paul (Blackwell Publishing, 2007)
It is widely reported that the main determinant of success at university is the score on university entrance exams. Recent studies have argued that the outcomes at university also differ according to the type of high school attended. This paper examines the impact of attending a non-Government school on the marks of first-year university students. Non-Government school students are found to have lower marks at university than Government school students, with the mark differential being slightly larger for those who do not perform well at tertiary study. The main factors influencing the size of the gap between the university marks of students from Government and non-Government schools are university entrance exam results and attendance at same-sex high schools.